Keterkaitan Pola Asuh Otoriter dengan Children Well-Being Anak di Kampung Pedesaan - Ai Asti Ramjani; Risbon Sianturi; Taopik Rahman (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study seeks to explore the relationship between authoritarian parenting and children’s well-being in rural village contexts. Authoritarian parenting refers to a parenting style marked by strict regulations, high levels of control, and minimal reciprocal communication between parents and children. Within rural communities, this approach is still frequently applied, influenced by cultural norms, inherited traditions, and socio-economic factors. The study adopts a qualitative design with a case study approach. Data were gathered through observations, interviews, and documentation involving several families residing in rural areas. The results show that authoritarian parenting is linked to various aspects of children’s well-being, particularly in emotional and social domains. Children raised in such environments are generally obedient and show a high level of discipline. However, they also tend to have lower self-confidence, face challenges in expressing their thoughts, and possess limited social interaction abilities. At the same time, some positive outcomes, such as strong discipline, are evident due to the strict parenting practices. Overall, the findings highlight that authoritarian parenting brings both positive and negative consequences for child development. It can be concluded that there is a meaningful relationship between authoritarian parenting and children’s well-being in rural settings. Children’s well-being is influenced not only by discipline but also by the strength of emotional connections between parents and children. Therefore, it is important to adopt a more balanced parenting style that combines discipline with emotional support to promote optimal child development and well-being